1997
DOI: 10.1007/bf02256089
|View full text |Cite
|
Sign up to set email alerts
|

Antifriction basalt-plastics based on polypropylene

Abstract: A study is made of the dependence of the mechanical and friction-engineering properties of polypropylene reinforced with basalt fibers on the viscosity of the polymer matrix. It is established that the main factors that determine the mechanical properties of the plastics are the quality of impregnation of the fibers by the binder and the residual length of the reinforcing filler in the composite after extrusion and injection molding. The material that was developed has a low friction coefficient and low rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…The matrix plays a key role in improving the mechanical properties of basalt fiber‐reinforced polymer composites mostly using polypropylene (PP), polyethylene, phenol‐formaldehyde, and epoxy resin as matrices. By reinforcing PP with chopped basalt fibers, Bashtannik and Ovcharenko found that basalt/PP composites were comparable to glass‐ and asbestos‐reinforced composites. Ronkay and Czigány prepared basalt/PET and glass/PET composites, and compared their bending, tensile, and impact strengths.…”
Section: Introductionmentioning
confidence: 99%
“…The matrix plays a key role in improving the mechanical properties of basalt fiber‐reinforced polymer composites mostly using polypropylene (PP), polyethylene, phenol‐formaldehyde, and epoxy resin as matrices. By reinforcing PP with chopped basalt fibers, Bashtannik and Ovcharenko found that basalt/PP composites were comparable to glass‐ and asbestos‐reinforced composites. Ronkay and Czigány prepared basalt/PET and glass/PET composites, and compared their bending, tensile, and impact strengths.…”
Section: Introductionmentioning
confidence: 99%
“…One possible substitute might be basalt fibers (BFs), which make it possible to create a composite with good service properties that is low in cost and less toxic. 23 BF-reinforced composites are increasing in technological importance due to their unique properties and high performance. BFs are produced by melt spinning technology from naturally existing basalt rock.…”
Section: Introductionmentioning
confidence: 99%
“…His also concluded that basalt fiber reinforced polymer have an excellent wear properties [6][7][8] . Jancar [9] investigated the effect of moisture on the flexural modulus, strength and ultimate strain of thermoplastic composites reinforced with unidirectionally aligned basalt fibers, in the directions parallel and perpendicular to the fiber orientation.…”
Section: Introductionmentioning
confidence: 99%